Buyers, Maybe Moving Second Is Not That Bad After All: Low-Power, Anxiety, and Making Inferior First Offers - Maaravi, Yossi; Heller, Ben (Frontiers in Psychology, 2021)
The behavioral decision-making and negotiations literature usually advocates a first-mover advantage, explained the anchoring and adjustment heuristic. Thus, buyers, who according to the social norm, tend to move second, strive to make the first offer to take advantage of this effect. On the other hand, negotiation practitioners and experts often advise the opposite, i.e., moving second. These opposite recommendations regarding first offers are termed the Practitioner-Researcher paradox. In the current article, we investigate the circumstances under which buyers would make less favorable first offers than they would receive were they to move second, focusing on low power and anxiety during negotiations. Across two studies, we manipulated negotiators’ best alternative to the negotiated negotiation (BATNA) and measured their anxiety. Our results show that, when facing neutral-power sellers, weak buyers who feel anxious would make inferior first offers (Studies 1 and 2). When facing low-power sellers, weak buyers would make inferior first offers across all anxiety levels (Study 2). Our findings shed light on two critical factors leading to the Practitioner-Researcher paradox: power and anxiety, and offer concrete guidelines to buyers who find themselves at low power and highly anxious during negotiations.